Clinical Status Asthmaticus as a Respiratory Emergency: Management in Pediatric and Adult Populations - Ramadhan, Panji Sena; Nursiain, Aziza Chantiqka Aulia; Wardana, Shira Putri; Salsabila, Tsania Zulfa; Larasati, Anak Agung Ayu Regina (Jurnal Biologi Tropis, 2025)
Status asthmaticus is a life-threatening acute asthma exacerbation that fails to respond to initial standard therapy and requires prompt, protocol-based emergency care. This article aims to determine the clinical status of asthma as a respiratory emergency: management in pediatric and adult populations. The article was compiled using a Systematic Literature Review (SLR) approach, combining current evidence and clinical guideline recommendations regarding the management of status asthmaticus in pediatric and adult populations. Status asthmaticus is a form of severe asthma exacerbation that is an emergency because it can lead to respiratory arrest and death if not treated promptly. Patients generally present with complaints of progressive shortness of breath, cough, wheezing, and signs of respiratory failure such as tachypnea, accessory muscle retractions, and in severe cases, decreased consciousness. Symptoms in children are usually more dramatic due to narrower airways, while in adults the main risks are respiratory muscle fatigue and ventilation complications. Initial management includes airway stabilization, oxygen administration, and immediate initiation of a short-acting bronchodilator (nebulized beta-agonist/MDI). If improvement does not occur, inhaled anticholinergics and systemic corticosteroids are added. Thus, in both children and adults, status asthmaticus requires early recognition, rapid treatment, and close evaluation until the condition is fully stabilized. Continuous monitoring with pulse oximetry and arterial blood gas analysis is emphasized as essential for detecting deterioration. Early recognition and rapid escalation following standard emergency pathways are crucial to reducing morbidity and mortality in both age groups.